Risk for exercise addiction: A comparison of triathletes training for sprint-, Olympic-, half-Ironman-, and Ironman-distance triathlons - Youngman, J.; Simpson, D. (Journal of Clinical Sport Psychology, 2014)
Researchers have noted that when taken to an excessive level, exercise may become addictive. This study investigated the risk of exercise addiction for triathletes using the Exercise Addiction Inventory (EAI; Terry, Szabo, & Griffiths, 2004). The sample consisted of 1,285 male and female triathletes, ranging in age from 18-70 years old. Results indicated that approximately 20% of triathletes are at risk for exercise addiction, and that training for longer distance races (i.e., Olympic, Half-Ironman, and Ironman) puts triathletes at greater risk for exercise addiction than training for shorter races (i.e., Sprint). No significant association was found between the risk for exercise addiction and the number of years of participating. However, as the number of weekly training hours increased, so did a triathlete`s risk for exercise addiction. At-risk triathletes need greater clinical attention, and further research should be conducted to help clinicians develop awareness and appropriate interventions.